Ask a question
0 0

c=(1/3)f(s+k) for s

i need to solve this formula for the specified variable of s.

Tutors, please sign in to answer this question.

2 Answers

     c = (1/3)f(s + k)

First, multiply both sides of the equation by 3 to get rid of the leading coefficient, (1/3), on the right-hand side of the equation:

     3·(c) = 3·((1/3)f(s + k))

        3c = (3/3)f(s + k)

       3c = f(s + k)

Divide both sides of the equation by f:

     (3c)/f = (f(s + k))/f

       3c/f = (f/f)(s + k)

     3c/f = s + k

Subtract k from both sides of the equation to solve for s:

            (3c/f) - k = (s + k) - k

      (3c/f)  -  k  =  s

I'm assuming f is just a variable here, and not meaning a function of some variable s+k. In that case, I would need more information like what the function is.

c = (1/3)f(s+k)

Let's multiply out the right hand side to easily get access to our variable s.

c = (1/3)fs + (1/3)fk

Subtract (1/3)fk from each side.

(1/3)fs = c - (1/3)fk

Multiply each side by 3.

fs = 3c - fk

Here, we'll have to assume that f does not equal 0 and is never equal to 0. Divide both sides by f.

s = (3c/f) - k

And here is our answer, s in terms of our other given variables.